PENGEMBANGAN INSTRUMEN ASESMEN BERBASIS DIGITAL SEBAGAI UPAYA MEMINIMALISIR KECURANGAN DALAM PELAKSANAAN UJIAN - Resi Agustien (At Turots: Jurnal Pendidikan Islam, 2025)
This research aims to design and develop digital-based assessment instruments to minimise cheating in the implementation of exams and wants to know the effectiveness of the development of digital-based assessment instruments in minimising cheating. The method used in this research is the Research and Development method with the ADDIE development model, namely analysis, design, develop, implement, and evaluate. The subjects in this study were material experts, media experts, and students of PAI study programme class C-D in the second semester of academic year 2024/2025. The object of development in this study is a digital-based assessment instrument with a descriptive quantitative approach. The data collection instrument uses a questionnaire which is used to collect quantitative data. The results of this study explain that the validity of the development of digital-based assessment instruments as an effort to minimise cheating in the implementation of exams has been tested valid and feasible to use. At the validation stage, media or IT experts gave an average score percentage of 78% (good) and at the material expert validation stage obtained an average score of 88% (very good) with the conclusion that this assessment instrument was feasible to use. The results of the effectiveness test stated that the score on the implementation of the post-test was smaller than the pre-test with a score difference of 25.96, which means that the development of digital-based assessment instruments is proven to prevent and minimise the level of cheating.